Teknologi Informasi dalam Pendidikan Formal dan Non Formal - Muhammad Sofwan; Wahyuddin Nur Nasution; Muhammad Irwan Padli Nasution (Tarbiatuna: Journal of Islamic Education Studies, 2025)
This study examines the role and impact of Information and Communication Technology (ICT) in the context of formal and non-formal education. Technology, broadly defined as a symbol of knowledge and a means by which humans build civilization, is now intrinsically linked to computer hardware and software in the realm of information. In formal education, ICT has transformed teaching and learning methods through online platforms such as Zoom and Google Classroom, accelerating learning processes, expanding access to diverse learning resources, and supporting distance learning, particularly during the pandemic. Nevertheless, challenges such as infrastructure limitations, varying user preferences, and alignment with local values remain obstacles. On the other hand, in non-formal education, ICT acts as a key facilitator in providing access to digital skills training relevant to the job market, promoting self-directed learning through online platforms, and strengthening digital competencies. A case study at LPK Anita illustrates how the adoption of modern technology can enhance administrative efficiency, improve learning quality, and create entrepreneurial opportunities. However, non-formal education also faces similar challenges, including limited infrastructure, a lack of human resource competence, insufficient funding, and suboptimal strategic management. This study concludes that ICT is an essential effort to deliver information and optimize learning, but its successful implementation heavily depends on proactive management of the various existing barriers.